It's Not Just Narrowing, It’s Instability! Why Cardiologists Need to Focus on Plaque Vulnerability, Enhanced by Drug-Coated Balloon Therapy and Whole-Food Plant-Based Diets - Mulijono, Dasaad (Cardiology and Cardiovascular Medicine, 2025)
Traditional cardiovascular risk assessment primarily focuses on identifying and managing significant luminal stenoses. Emerging clinical evidence, however, increasingly underscores plaque vulnerability (PV) as a superior predictor of acute coronary syndromes (ACS) compared to stenosis severity alone. Advanced imaging techniques, particularly coronary computed tomography angiography (CCTA) and fractional flow reserve derived from computed tomography angiography (FFRCT), reveal that the characteristics of vulnerable plaque (VP) significantly elevate cardiovascular risk, independent of lesion stenosis severity. This article advocates a paradigm shift toward prioritizing PV in cardiovascular risk assessment, integrating innovative therapeutic approaches such as Drug-Coated Balloon (DCB) therapy and Whole-Food Plant-Based Diets (WFPBD). Observational data from Bethsaida Hospital, guided by Prof. Dasaad Mulijono, involving nearly a couple thousand patients managed with DCB angioplasty combined with WFPBD, demonstrate markedly superior clinical outcomes, including minimal major adverse cardiovascular events (MACE), absence of mortality, significantly lower restenosis rates (2% compared to the national average of 10–20%), and elimination of stent thrombosis. Integrating advanced biomarker assessments [high-sensitivity C-reactive protein (hs-CRP), oxidized LDL, trimethylamine-N-oxide (TMAO), salivary nitric oxide (NO) levels] further enhances predictive accuracy, enabling precise risk stratification and personalized preventive strategies. This comprehensive, biologically focused approach provides a robust framework for revolutionizing cardiovascular care.